Bioactive compounds of Chloranthus officinalis are successfully characterised as potential dengue antivirals - Munawir Sazali; Mohan Taufiq Mashuri; Fikrul Yakin; Arina Ulya Asari; Dini Justitia Ningsih; Muhsinul Ihsan; Muhammad Faisyal; Arif Nur Muhammad Ansori (Universitas Islam Negeri Sumatera Utara, 2026)
While Chloranthus officinalis, a medicinal plant has been widely used in Rinjani Mountain National Park, its bioactive compounds have not yet been characterised. This study aims to characterise the bioactive compounds of C. officinalis. Biocative compounds from C. officinalis were extracted with 96% ethanol and analysed by GC-MS; further analysis using Toxtee software was used to determine toxic activity. There were 18 bioactive compounds in C. officinalis, five of them (quercetin, terpinen-4-ol, δ-cadinene, α-cadinol, and viridiflorol) have potential candidate dengue antivirals. The toxicity level of Quercetin, Terpinene-4-ol, and Viridiflorol are in class 3 (LD50 values 1500-2000 mg/kg), while δ-cadinene and α-Cadinol are class 4 (LD50 2500-5000 mg/kg). Five potential bioactive compounds in C. officinalis have antiviral activity against dengue fever. Overall, these findings indicate that C. officinalis contains bioactive compounds with a favourable safety profile for oral consumption, supporting its use in traditional medicine.